Regional disparities in primary cesarean delivery rates in Japan: the role of obstetrician availabilityAJOG Global Reports at a Glance - Akihiko Ueda, MD; Baku Nakakita, MD; Yoshitsugu Chigusa, MD, PhD; Haruta Mogami, MD, PhD; Genta Kato, MD, PhD; Hiroaki Ueshima, PhD; Masaki Mandai, MD, PhD; Eiji Kondoh, MD, PhD (Elsevier, 2024)
Background: The prevalence of cesarean section procedures is on the rise worldwide, necessitating a deeper understanding of the factors driving this trend to mitigate potential adverse consequences associated with unnecessary cesarean section deliveries. Objectives: This study aims to investigate the rate of primary cesarean deliveries (PCD), a potential key indicator of obstetric care quality. Study Design: A national retrospective cohort study was conducted utilizing extensive data from the National Database of Health Insurance Claims and Specific Health Checkups of Japan spanning the years 2012 to 2018. The study examined the temporal trends in PCD rates and the indications for these procedures across different prefectures. Additionally, the study employed the obstetrician disproportionality index, as published by the Ministry of Health, Labour, and Welfare, to assess the influence of obstetrician availability on PCD rates. Results: Throughout the study period from 2012 to 2018, the rate of PCD in Japan remained relatively stable at approximately 14%. The primary indications for PCD in 2018 included labor arrest (18.3%), malpresentation (16.5%), nonreassuring fetal status (6.5%), and macrosomia (6.0%). Substantial regional disparities in PCD rates were observed, ranging from 8.9% to 20.4% among prefectures in 2018. Notably, prefectures categorized in the bottom 10 of the obstetrician disproportionality index exhibited significantly higher PCD rates compared to the top 10 prefectures (P=.0232), with a similar trend noted for PCD due to labor arrest (P=.0288). Furthermore, a negative correlation was identified between the obstetrician disproportionality index and PCD rates at the prefectural level (r=-0.3119, P=.0328). Conclusions: Our study presents a comprehensive analysis of PCD rates in Japan, shedding light on regional disparities and highlighting the notable influence of obstetrician availability on clinical decision-making. This study contributes to the ongoing discourse on the escalating global trend in cesarean sections and the importance of healthcare resource allocation in maternal care.